2018
DOI: 10.1038/s41467-018-05339-6
|View full text |Cite
|
Sign up to set email alerts
|

The conformational wave in capsaicin activation of transient receptor potential vanilloid 1 ion channel

Abstract: The capsaicin receptor TRPV1 has been intensively studied by cryo-electron microscopy and functional tests. However, though the apo and capsaicin-bound structural models are available, the dynamic process of capsaicin activation remains intangible, largely due to the lack of a capsaicin-induced open structural model and the low occupancy of the transition states. Here we report that reducing temperature toward the freezing point substantially increased channel closure events even in the presence of saturating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 67 publications
6
69
0
1
Order By: Relevance
“…Therefore, voltage activation cannot be carried out through the same transition promoted by capsaicin, i.e., if Scenario B is true, capsaicin cannot be stimulus X . Indeed, as capsaicin induces TRPV1 activation by linking S4 to the S4-S5 linker 42-44 , these results offered further supports for the conclusion that voltage activation does not involve S4. Furthermore, the observation of a voltage-independent, elevated P o in the presence of capsaicin also validated the conclusion that voltage cannot work through the C↔O transition to open the channel, i.e., Scenario A is invalid.…”
Section: Identifying the Voltage-dependent Transitionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, voltage activation cannot be carried out through the same transition promoted by capsaicin, i.e., if Scenario B is true, capsaicin cannot be stimulus X . Indeed, as capsaicin induces TRPV1 activation by linking S4 to the S4-S5 linker 42-44 , these results offered further supports for the conclusion that voltage activation does not involve S4. Furthermore, the observation of a voltage-independent, elevated P o in the presence of capsaicin also validated the conclusion that voltage cannot work through the C↔O transition to open the channel, i.e., Scenario A is invalid.…”
Section: Identifying the Voltage-dependent Transitionsupporting
confidence: 61%
“…Small cations such as proton, Na + and Mg 2+ /Ba 2+ /Ni 2+ /Gd 3+ , as well as large peptide toxins such as DkTx, RhTx and BmP01 all bind to this region to exert their strong gating effects 48 . Capsaicin activation has been recently found to affect the outer pore 44 . Heat also induces large conformational changes of the outer pore 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Key atomic interactions include two hydrogen bonds-formed between the amide group in the capsaicin neck and the hydroxyl group of T551 on the S4 segment of the TRPV1 channel (using mTRPV1 amino acid number) and between the hydroxyl group in the capsaicin head and the carboxyl group of E571 on the S4-S5 linker-as well as extensive van der Waals (VDW) interactions including those by the capsaicin tail. Accuracy of the current capsaicin binding model has been satisfactorily confirmed by studies of the structural correlates of deactivation kinetics (Kumar et al, 2016), the activation conformational wave in TRPV1 channels triggered by capsaicin binding (Yang et al, 2018), the evolutionary drive for the tree shrew's insensitivity to spiciness (Han et al, 2018), and the rational designs of vanilloid-sensitive TRPV2 channel mutants (Yang, Vu, Yarov-Yarovoy, & Zheng, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Indeed, the average Rosetta energy for hydrogen bond of the top models was substantial at this position(Figure 6c, bottom panel). This interaction, if formed, would contribute to the stabilization of ligand binding and, given the role played by the S6 segment in activation of the TRPV1 channel(Yang et al, 2018;Zheng & Ma, 2014), may even represent a new way to stabilize the channel's open conformation. Overall, our structural modelling results confirmed that zingerone is much less stable inside the ligand-binding pocket and, as a result, a weak agonist for the TRPV1 channel.…”
mentioning
confidence: 99%
“…In addition to the identifying topological features, a number of TRPV1 structures in different states have been determined, which have provided significant insight into the molecular basis for TRPV1 chemical activation (19)(20)(21). Canonical TRPV1 vanilloid compounds, like the pungent agonist capsaicin, bind to the S1-S4 domain which couples with the PD to open the lower and upper gates of the channel (22), thereby initiating signal transduction. The cryo-EM determined vanilloid binding site (19)(20)(21) is consistent with previous studies (23)(24)(25)(26)(27)(28), which identified residues in the S3 and S4 helices of the TRPV1 S1-S4 domain as central for capsaicin activation.…”
Section: Introductionmentioning
confidence: 99%